The Effect of the Problem-Based Learning (PBL) Model with a Multimodal Approach on Students' Physics Conceptual Understanding - Shelliana Iqlima; Gunawan Gunawan; Muhammad Zuhdi (Indonesian Publication Center, 2026)
This study aims to examine the effect of the Problem-Based Learning (PBL) model with a multimodal approach on students' physics conceptual understanding on the static fluid topic. The study was motivated by the low conceptual understanding of eleventh-grade students at SMAN 3 Praya, resulting from conventional instruction that rarely engaged students in problem-solving activities and lacked varied learning representations. This research employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of 26 students in the experimental group and 28 students in the control group, determined through purposive sampling. Conceptual understanding data were collected using a multiple-choice test based on the six levels of the revised Bloom's Taxonomy, namely remembering, understanding, applying, analyzing, evaluating, and creating, then analyzed using a pooled-variance t-test. The results showed that the experimental group posttest mean score of 85.42 was higher than the control group score of 78.42, with tcount of 2.952 greater than ttable of 2.007 at a 5% significance level. The N-Gain test revealed that the experimental group achieved a high category (0.769), higher than the control group which was in the moderate category (0.645). Therefore, it can be concluded that the PBL model with a multimodal approach has a significant effect on students' physics conceptual understanding.